Tren Kecantikan dalam Perspektif Hadis - Muhammad Bilal Fauzi; Salim Rosyadi (Al-Mu'tabar, 2024)
Beauty trends are actions that can reflect the values or views that prevail in society regarding perceptions of beauty, this gives rise to a new culture that is followed by society. This article aims to provide the boundaries of moral values that are in accordance with Islamic sharia through a review of hadith. This research uses a contemporary hadith thematic method by applying the grounded theory method. There are 6 hadiths found from the Maktaba Shameela or the Hadith Book of 9 Imams. The hadiths found were narrated by Sahih Bukhari, Sahih Muslim, Sunan Tirmidhi, and Sunan Ahmad. This research concludes that beauty trends are permissible from a religious perspective, as long as the actions do not deviate from the sharia values taught in Islamic guidelines (Al-Quran and Hadith).